Patients’ perceptions and experiences of patient safety in primary care in England - Cabello, I; Pons-Vigués, M; Berenguera, A; Pujol-Ribera, E; Slight, S; Valderas, J (Oxford University Press, 2016)
Background One of the most remarkable features of patient safety research in primary care is the sparse attention paid to patients’ own experiences. Objective To explore patient’s perceptions and experiences of patient safety in primary care in England. Methods We conducted a qualitative study in the South of England with an opportunistic sample of 27 primary care users. Information was obtained from four patient focus groups. A thematic content analysis was conducted by three analysts and consensus reached within the research team on the key themes that emerged. Results Participants’ conceptualizations of patient safety referred to high standards of healthcare delivery within a relationship of trust. Participants identified four main factors that they believed could potentially affect patient safety. These included factors related to: 1) the patient (attitudes, behaviours, and health literacy), 2) the health professional (attitudes, behaviours and accuracy of diagnoses), 3) the relationship between patients and health professionals (communication and trust), and 4) the healthcare system (workload, resources, care coordination, accessibility, interdisciplinary teamwork, and accuracy of health care records). Confidentiality, continuity of care and treatment-related safety emerged as cross-cutting major threats to patient safety. Conclusion The exploration of participants’ perceptions and experiences allowed the identification of a wide variety of themes that were perceived to impact on patient safety in primary care. The findings of this study could be used to enrich current frameworks that are exclusively based on professional or healthcare system perspectives.